Neuroinflammation and Copper in Alzheimer's Disease. (28th November 2013) - Choo, Xin Yi; Alukaidey, Lobna; White, Anthony R.; Grubman, Alexandra
Abstract : Inflammation is the innate immune response to infection or tissue damage. Initiation of proinflammatory cascades in the central nervous system (CNS) occurs through recognition of danger associated molecular patterns by cognate immune receptors expressed on inflammatory cells and leads to rapid responses to remove the danger stimulus. The presence of activated microglia and astrocytes in the vicinity of amyloid plaques in the brains of Alzheimer's disease (AD) patients and mouse models implicates inflammation as a contributor to AD pathogenesis. Activated microglia play a critical role in amyloid clearance, but chronic deregulation of CNS inflammatory pathways results in secretion of neurotoxic mediators that ultimately contribute to neurodegeneration in AD. Copper (Cu) homeostasis is profoundly affected in AD, and accumulated extracellular Cu drives A β aggregation, while intracellular Cu deficiency limits bioavailable Cu required for CNS functions. This review presents an overview of inflammatory events that occur in AD in response to A β and highlights recent advances on the role of Cu in modulation of beneficial and detrimental inflammatory responses in AD.